Chapter Broadband NIRS Cerebral Evaluation of the Hemodynamic and Oxidative State of Cytochrome-c-Oxidase Responses to +Gz Acceleration in Healthy Volunteers - Lange, F. (Springer Nature, 2020)
We used a miniature broadband NIRS system to monitor concentration changes in brain oxygenation (oxy- and deoxy- haemoglobin [HbO2], [HHb]) and oxidised cytochrome-c-oxidase ([oxCCO]) during a high +Gz acceleration, induced by a human centrifuge, on two healthy experienced volunteers (2 male, 34 and 37 years). We performed a sequence of several +Gz exposures that were terminated at the onset of visual symptoms (loss of peripheral vision). Systemic parameters were recorded (i.e. heart rate, blood pressure and arterial saturation), and brain tissue blood volume changes ([HbT] = [HbO2] + [HHb]) and oxygen delivery ([HbDiff] = [HbO2] - [HHb]) were calculated. Volunteer 1 demonstrated a decrease in [HbT] of −3.49 ± 0.02 μMol and [HbDiff] of −3.23 ± 0.44 μMol, and an increase of [oxCCO] of 0.42 ± 0.01μMol. Volunteer 2 demonstrated a decrease in [HbDiff] of −4.37 ± 0.23 μMol, and no significant change in [HbT] (0.53 ± 0.06 μMol) and [oxCCO] (0.09 ± 0.06 μMol). The variability of the brain metabolic response was related to the level of ischaemia, suggesting that suppression of metabolism was due to lack of glucose substrate delivery rather than oxygen availability.